The operas of Maurice Ravel - Kilpatrick, Emily 1983- (Music in context, 2015)
Maurice Ravel's operas L'Heure espagnole (1907/1911) and L'Enfant et les sortileges (1919-25) are pivotal works in the composer's relatively small oeuvre. Emerging from periods shaped by very distinct musical concerns and historical circumstances, these two vastly different works nevertheless share qualities that reveal the heart of Ravel's compositional aesthetic. In this comprehensive study, Emily Kilpatrick unites musical, literary, biographical and cultural perspectives to shed new light on Ravel's operas. In documenting the operas' history, setting them within the cultural canvas of their creation and pursuing diverse strands of analytical and thematic exploration, Kilpatrick reveals crucial aspects of the composer's working life: his approach to creative collaboration, his responsiveness to cultural, aesthetic and musical debate, and the centrality of language and literature in his compositional practice. The first study of its kind, this book is an invaluable resource for students, specialists, opera-goers and devotees of French music. - Emily Kilpatrick holds a PhD in Musicology from the University of Adelaide, and has published widely on the music of Ravel and Faure. She is co-editor, with Roy Howat, of the new Peters critical edition of Faure's complete songs, a project based at the Royal Academy of Music in London. Emily also maintains an active performing career as a pianist and vocal accompanist, and regularly gives recitals, radio broadcasts, master classes and lectures on French opera and song.